Some Unified Form of Open Sets and Continuity In Ideal Minimal Spaces - Noiri, Takashi; Popa, Valeriu (Sarajevo Journal of Mathematics, 2022)
We introduce the notion, of, umIO(X)-structures determined by operators mInt, mCl, mInt^ and mCl^ on an ideal minimal space (X, m_X, I). By using umIO(X)-structures, we introduce and investigate a function f : (X, m_X, I) → (Y, σ) called umI-continuous. As special cases, of, umI-continuity, we obtain m-semi-I-continuity JRS, m-pre-I-continuity [10], m-α-I-continuity CGJNR, m-b-I-continuity Ma-Mu, and m-β-I-continuity [9].